Scaling Up Domestic Resource Mobilization Via Non-Tax Revenues: Is The Government Directive Sustainable? - Njau, Adrian Peter; Kombe, Wilbard Jackson; Melyoki, Lemayon Lemilia (Universitas Muhammadiyah Yogyakarta, 2024)
The paper critiques Tanzania’s fifth phase government’s directive under then President John Pombe Magufuli aimed at boosting domestic resource mobilization through non-tax revenues. Using a descriptive qualitative method approach, it examines the directive’s impact on key institutions contributing to the Treasury Consolidated Fund. Analysis of data from various sources, including government reports and face-to-face interviews with key officials from the selected public institutions and statutory corporations, reveals mixed results: while some institutions improved revenue mobilization due to better governance and technology, others struggled, even dipping into limited funds to comply with the government directive; in turn, this lead to undermine the performance of some of the statutory institutions in meeting their obligations. The study suggests that sustainable non-tax revenue strategies require institutionalized policies aligned with enhanced institutional capacities. It highlights the importance of efficient use of resources for socio-economic development. The paper underlines the ongoing reforms under the Office of the Treasury Registrar to transform the office into a Public Investment Management Authority, aiming at improving the institutionalization of non-tax revenues, boosting the performance effectiveness and non-tax revenue collection. It calls for long-term, standardized approaches to non-tax revenue mobilization for sustainable development. It cautions against the adoption of ad hoc measures that may adversely affect the performance of public institutions. This study is significant to the scholarship on governance and resource mobilization and cautions leaders and policymakers about the consequences of their decisions.